Pengaruh Youtuber Gadget Review, Desain, Customer Trust dan Kelengkapan Fitur Terhadap Minat Beli Smartphone Samsung - Damayanti, Erika; Rizal, Mohammad; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to analyze the influence of YouTuber gadget reviews, design, customer trust and completeness of features on Samsung smartphone buying interest". Using a quantitative approach, this research was conducted among students of the Islamic University of Malang. Data collection methods include distributing questionnaires via googleform to respondents. The sample used was 86 respondents. The results showed that YouTuber gadget reviews did not have a significant influence on Samsung smartphone buying interest, design did not have a significant influence on Samsung smartphone buying interest, customer trust had a significant influence on Samsung smartphone buying interest, and feature completeness had a significant influence on Samsung smartphone buying interest. This research provides valuable insights for Samsung's smartphone company in designing effective marketing strategies amid intense competition in the technology industry. Keywords: Youtuber Gadegt Review, Design, Customer Trust, Feature Completeness and Purchase Interest